Profil Kebermaknaan Hidup Siswa Membolos - Putri, Viqri Novielza; Ifdil, Ifdil; Yusri, Yusri; Yendi, Frischa Meivilona (Universitas Negeri Padang, 2020)
Traunt behavior is a negative bahavior in students that does not reflect the meaning of life, where the meaning of life is characterized by positive attitude and behaviors aimed at the future. The meaning of life is an individual condition that lives positively and passion to achieve the goal set. This paper aims to describe the concepts of the meaning of life, aspects of the meaning of life, factors of the meaning of life, and it’s relation to traunt student behavior. The method used the study literature, and data analysis technique use is by observation and interviews. The result of the discussion aimed that traunt students had a low meaningful life. This show that the meaning of life is very important for students to have a good behavior aimed at their future. The provision of counseling services by guidance and counseling teachers in school can help students to have the meaning of life.